Ab initio nonorthogonal valence bond methods. (12th July 2012) - Su, Peifeng; Wu, Wei
Abstract Modern classical valence bond (VB) methods provide clear interpretation and chemical insights by employing covalent and ionic VB structures explicitly. This review focuses on a methodical development of current modern classical VB methods. As a basic method of the classical VB theory, the VB self‐consistent field (VBSCF) method provides a compact wave function, mainly containing static correlation. On the basis of the VBSCF method, the development of classical VB methods can be divided into two aspects—one focuses on improvement of computational accuracy, such as the breathing orbital VB (BOVB), VB configuration interaction (VBCI), and VB second‐order perturbation theory (VBPT2) methods; the other focuses on extending VB approaches to molecules and reactions in solvated or biological environments, including the VB polarizable continuum model (VBPCM), VB solvation model (VBSM), VB effective fragment potential (VBEFP), and VB/molecular mechanics (VB/MM) methods. These improved methods have the advantage of VB theory and provide intuitive chemical insights into medium‐sized chemical problems. Finally, the further development of modern classical VB methods is briefly discussed.